Gender differences in eating behavior and eating pathology: The mediating role of rumination. (1st March 2017) - Opwis, Mareile; Schmidt, Jennifer; Martin, Alexandra; Salewski, Christel
Abstract: Objective: Rumination is a maladaptive emotion regulation strategy which contributes to psychopathology and is more frequently used by women than men. It has been found to mediate the relationship between gender and the occurrence of anxiety disorders or depression. Since gender differences also appear in dysfunctional eating, the aim of the study is to test, whether rumination mediates the association between gender and several facets of eating pathology. Method: A total of 295 participants (205 women) completed an online-questionnaire including the assessment of different facets of dysfunctional eating and rumination. Mediation analyses were conducted with PROCESS. Results: Women reported significantly higher levels in both, rumination and eating pathology. Moreover, rumination mediated the relationship between gender and all assessed aspects of dysfunctional eating. Discussion: The present study extends findings on the mediating role of rumination accounting for gender differences in psychopathology to eating pathology in a community sample. Results suggest that cognitive factors play a substantial role in explaining gender differences in eating pathology which tend to be reduced to biologicals factors and beauty ideals.